A new grid side inertia support control method for cascaded power converters in Bi-directional EV chargers - Tian, Yan; Huang, Bo; Fang, Jian; Chen, Wei; Xin, Yu; Lin, Haobo; Lin, Xiang (Frontiers in Energy Research, 2024)
To provide inertia support to the power grid, the grid side frontend DC/AC inverter of the bidirectional electric vehicle (EV) charging facilities can use the virtual synchronous generator (VSG) control in its grid-side DC/AC converter. However, the existing VSG control cannot actually realize the inertia support due to the limitations of the existing cascaded power converters control structure of the bidirectional EV charger. This paper proposes a new control infrastructure for VSG based bi-directional EV charging facilities. The proposed control instantaneously tracks the inertial supporting surge power by DC/DC so as to stabilize the DC bus voltage. Meanwhile, the droop coefficient based power values are also fed forward to DC/DC controls to support grid frequency control over a larger time scale. Finally, the experiment results show that the proposed method improves the DC bus voltage stability of the EV charger while allowing the EV to participate in the power system frequency regulation, which is a key feature of the Vehicle to Grid applications.